Association of Psychosocial Factors With Shoulder Tendinitis: A Cross-Sectional Study in Patients of a Tunisian Hospital - Belhadj, Noura; Lahsini, Malek; Mahfoudh, Aouatef; Khalfallah, Taoufik (La Medicina del Lavoro, 2025)
Background: To assess the association between rotator cuff  tendinitis (RCT) occurrence and socio-professional constraints among a sample of professionally active patients. Methods: This study was based on a questionnaire that collected information on sociodemographic, occupational characteristics, and medical information about shoulder injuries. The assessment of psychosocial constraints at work was performed using the Karasek Job Content Questionnaire. Results: A total of 100 patients participated in this study. The population was predominantly female (89%), with a mean age of 45±9.5 years. Sixty-five percent of the patients worked in the manufacturing sector, and working as a machine operator was the most common occupation (48%). The average job seniority was 22±9 years. Regarding organization, the most common constraints were the need to respect production standards and deadlines (93%), to work quickly in 96% of cases, and Repeatability (92%). Eighty-eight percent of the patients reported high psychological demands, and 96% had low social support at work. Most of the patients (83%) were under occupational stress or had been subjected to a job-strain situation. Discussion: In this study, high psychological demand, low decision latitude, and low social support were predominantly reported in the population with percentages of 88%, 93%, and 96%, respectively.